Derivatives Use and Risk Taking: Evidence from the Hedge Fund Industry - Chen, Yong (Journal of Financial and Quantitative Analysis, 2011)
Abstract This paper examines the use of derivatives and its relation with risk taking in the hedge fund industry. In a large sample of hedge funds, 71% of the funds trade derivatives. After controlling for fund strategies and characteristics, derivatives users on average exhibit lower fund risks (e.g., market risk, downside risk, and event risk), such risk reduction is especially pronounced for directional-style funds. Further, derivatives users engage less in risk shifting and are less likely to liquidate in a poor market state. However, the flow-performance relation suggests that investors do not differentiate derivatives users when making investing decisions.